Mechanical Characterization of Composite Coatings Formed by Reactive Detonation Spraying of Titanium; Metals; Vol. 7, iss. 9 - Panin S. V. Sergey Viktorovich; Vlasov I. V. Ilya Viktorovich; Dudina D. V. Dina Vladimirovna; Uljyanitsky V. Yu. Vladimir Yurjevich; Stankevich R. V. Roman Vladimirovich; Batraev I. S. Igor Sergeevich; Berto F. Filippo (2017, 2017)
Title screen